Combining a pyclen framework with conjugated antenna for the design of europium and samarium luminescent bioprobes. Issue 48 (30th May 2018) - Hamon, Nadège; Galland, Margaux; Le Fur, Mariane; Roux, Amandine; Duperray, Alain; Grichine, Alexei; Andraud, Chantal; Le Guennic, Boris; Beyler, Maryline; Maury, Olivier; Tripier, Raphaël
Abstract : Pyclen-based ligand bearing picolinate ILCT antenna forms highly luminescent one- and two-photon Eu(iii ) and Sm(iii ) complexes. Abstract : The first pyclen based ligand bearing two picolinate intra-ligand charge transfer transition antennae and one acetate arm organized in a dissymmetric manner was synthesized for Eu(iii ) and Sm(iii ) complexation. The europium complex presents an excellent brightness and biphotonic imaging of T24-cells has been performed using Eu(iii ) and the less common Sm(iii ) bioprobes.